Mali : Poverty Reduction and Strategy Paper-2009 Progress Report. (IMF Staff Country Reports; Country Report ;, 2011)
Poverty Reduction Strategy Papers (PRSPs) are prepared by the member country in broad consultation with stakeholders and development partners. Despite strong economic performance in recent years compared with Sub-Saharan African and WAEMU countries, Mali's average annual growth rate of 4.6 percent is below the target of 7 percent provided in the PRSP. At end-2009, the situation in the banking and financial system was characterized by an increase in the money supply, an increase in net foreign assets, an increase in credit to the economy, and a decline in credit to the government.